Faktor - Faktor Yang Berpengaruh Terhadap Pinjaman Daerah Pada Kota/Kabupaten di Provinsi Jawa Timur - Muhammad Bahril Ilmidaviq (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2018)
The purpose of this study was to analyze the influence of factors such as Per Capita Income, Population, PAD, Government Transfer Funds, Capital Expenditures, Surplus / Budget Deficits and Political Factors on Regional Loans in Districts / Cities in East Java. The sample used in the study is the District / City in East Java that has Regional Loans in a row for three years. The data used is data for 2014-2016. This study uses Multiple Linear Regression to examine the effect between variables. The results of the study show that Capital Expenditures, Government Transfer Funds and political factors have a positive influence on Regional Loans. Per Capita Income, Population Amount, Surplus / Budget Deficit and PAD does not affect Regional Loans